Implementation Of Policy Accelerate The Implementation Of Complete Systemic Land Registration (PTSL) At The National Land Agency Of Medan City - Tongam Nadeak (IHSA Institute, 2020)
The policy for the Acceleration of Complete Systematic Land Registration (PTSL) carried out by the Government based on the Minister of Agrarian Regulation No. 1 of 2017 is generally a land registration activity for the first time that is carried out simultaneously which includes all land registration objects that have not been registered in one village/kelurahan area. or other names at the same level in order to guarantee legal certainty and legal protection of people's land rights in a fair and equitable manner. The title of this research is the implementation of the Policy for the Acceleration of Complete Systematic Land Registration (PTSL) at the National Land Agency of Medan City. The research method used in this study is a qualitative approach with descriptive analysis techniques that describe the actual phenomenon of events in the field with the Merilee S Grindle theoretical approach which suggests that the success of a policy is influenced by the content of policy variables and the policy environment (context of policy). ). The data collection technique used is Interview, Observation and Documentation related to Complete Systematic Land Registration (PTSL).The implementation of the policy for the Acceleration of Complete Systematic Land Registration (PTSL) by the National Land Agency of Medan City is going well even though the human resources or implementing personnel in the field are still lacking in quantity. So that the implementor in the field must work with an inappropriate workload.